2008
DOI: 10.1073/pnas.0708003105
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron targeting by self-complementary AAV8 via lumbar puncture for chronic pain

Abstract: Lumbar puncture (LP) is an attractive route to deliver drugs to the nervous system because it is a safe bedside procedure. Its use for gene therapy has been complicated by poor vector performance and failure to target neurons. Here we report highly effective gene transfer to the primary sensory neurons of the dorsal root ganglia (DRGs) with self-complementary recombinant adeno-associated virus serotype 8 (sc-rAAV8) modeling an LP. Transgene expression was selective for these neurons outlining their cell bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 34 publications
7
108
1
Order By: Relevance
“…Different serotypes of adeno-associated vectors (AAV) also transduce sensory neurons in the dorsal root ganglia (DRG) through direct administration into the cerebral spinal fluid or via retrograde transport. [3][4][5][6] Specific transduction of non-neuronal cell types in the PNS, particularly of Schwann cells, may be of great interest for the treatment of hypo-or de-myelinating diseases, diabetic neuropathy or to overexpress trophic factors for nerve regeneration. Transduction with first-generation adenovirus showed a broad but transient tropism in many tissues, including different cell types in the PNS.…”
Section: Introductionmentioning
confidence: 99%
“…Different serotypes of adeno-associated vectors (AAV) also transduce sensory neurons in the dorsal root ganglia (DRG) through direct administration into the cerebral spinal fluid or via retrograde transport. [3][4][5][6] Specific transduction of non-neuronal cell types in the PNS, particularly of Schwann cells, may be of great interest for the treatment of hypo-or de-myelinating diseases, diabetic neuropathy or to overexpress trophic factors for nerve regeneration. Transduction with first-generation adenovirus showed a broad but transient tropism in many tissues, including different cell types in the PNS.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies showed efficient targeting of primary sensory neurons and transgene expression for up to 4 months; 19,20 follow-up experiments found that transgene expression persisted undiminished for at least 15 months after gene transfer, the longest time point that we tested (unpublished).…”
Section: Favorable Characteristics: Targeting Of Non-dividing Cells Amentioning
confidence: 66%
“…The above discussed study 20 showed highly efficient and selective gene transfer into primary sensory neurons by administration of sc-rAAV8 vectors into the lumbar CSF. Transduction was selective for DRG neurons and did not affect other cells of the CNS.…”
Section: Conclusion From It Sc-raav Experiments In Rodentsmentioning
confidence: 89%
See 1 more Smart Citation
“…This approach would require a direct intraparenchymal injection of vectors rather than intrathecal administration, which tends to the predominant transduction of meningeal cells or DRG sensory neurons and only very modest transduction of spinal cord tissue. [13][14][15] Additionally, central nervous system (CNS) intraparenchymal injection of vector limits the systemic immune response, thus inducing only a negligible inflammatory response. 16 Lentiviral vectors as a potential tool for targeting spinal cord glia Lentiviral (LV) vectors appear to be the best candidates for targeting spinal cord glia.…”
mentioning
confidence: 99%